Young lives on the left : sixties activism and the liberation of the self - Hughes, Celia (Manchester University Press, 2015)
'Young Lives on the Left' is a unique social history of the individual lives of men and women who came of age in radical left circles in the 1960s. Based on a rich collection of oral history interviews, it follows approximately 20 individuals, tracing the experience of activist self-making from child to adulthood in depth.